2020
DOI: 10.2196/preprints.21176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 Epidemic on Lifestyle Behaviors and Their Association With Subjective Well-Being Among the General Population in Mainland China: Cross-Sectional Study (Preprint)

Abstract: BACKGROUND The world is experiencing an extraordinary, life-altering challenge due to the COVID-19 pandemic. However, it is unclear whether the lifestyle will change under the situations of COVID-19 epidemic. OBJECTIVE To explore perceived lifestyle changes, after the outbreak of coronavirus (COVID-19) disease, and their association with subjective wellbeing (SWB) among the general population i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
5
0
2
Order By: Relevance
“…Similarly, Górnicka found that 43% of respondents had a reduction in physical activity, and 34% had increased food consumption in a sample where 49% of individuals reported an increased screen time (Górnicka et al, 2020). A study from China assessed the physical and psychosocial health impacts during the nationwide lockdown and found that more than half of Chinese adults had a sedentary lifestyle with inadequate physical activity, increased screen time, and poor emotional state (Hu et al, 2020). These studies suggest that a synergistic effect may exist between these co-occurring health behaviors, which can be prevalent among individuals affected by this pandemic.…”
Section: Covid-19 and Rising Trends Of Screen Time: Public Health Conmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Górnicka found that 43% of respondents had a reduction in physical activity, and 34% had increased food consumption in a sample where 49% of individuals reported an increased screen time (Górnicka et al, 2020). A study from China assessed the physical and psychosocial health impacts during the nationwide lockdown and found that more than half of Chinese adults had a sedentary lifestyle with inadequate physical activity, increased screen time, and poor emotional state (Hu et al, 2020). These studies suggest that a synergistic effect may exist between these co-occurring health behaviors, which can be prevalent among individuals affected by this pandemic.…”
Section: Covid-19 and Rising Trends Of Screen Time: Public Health Conmentioning
confidence: 99%
“…A study of 254 Canadian families with young children reported an increase of screen time in mothers, fathers, and children during COVID-19 as 74%, 61%, and 87%, respectively (Carroll et al, 2020). Moreover, a study conducted in China found that about 70% of 1033 participants spent more time looking at screens after the COVID-19 outbreak (Hu et al, 2020). Another study used a longitudinal design to evaluate health behavior changes during COVID-19 and found a perceived increase in screen time among the participants (Keel et al, 2020).…”
Section: Covid-19 and Rising Trends Of Screen Time: Public Health Conmentioning
confidence: 99%
See 1 more Smart Citation
“…However, adolescents often lack nutrition knowledge, and most of them have unhealthy eating habits and unbalanced dietary patterns [26][27][28], and this phenomenon has become increasingly serious during the COVID-19 epidemic [4,[29][30][31][32]. Therefore, most adolescents may have a substantial risk for hidden hunger.…”
Section: Introductionmentioning
confidence: 99%
“…O exercício físico, realizado com estímulo adequado 1,2 , pode promover modificações em estruturas e funções do corpo como a redução de pressão sistólica e diastólica 3 , aumento da força muscular 4 , mudanças na diversidade da microbiota intestinal 5 e no volume e conectividade cerebral 6 . Tais mudanças podem ter efeito benéfico em indivíduos saudáveis, assim como em indivíduos com comorbidades e doenças crônicas [7][8][9][10] . No entanto, deve-se considerar que um protocolo de exercício agudo induz alterações transitórias, enquanto o treinamento físico estimula adaptações crônicas 11,12 .…”
Section: Introductionunclassified